Chance, Orientation, and Interpretation: Max Weber's Neglected Probabilism and the Future of Social Theory. (June 2022) - Strand, Michael; Lizardo, Omar
The image of Max Weber as an "interpretivist" cultural theorist of webs of significance that people use to cope with a meaningless world reigns largely unquestioned today. This article presents a different image of Weber's sociology, where meaning does not transport actors over an abyss of meaninglessness but rather helps them navigate a world of Chance . Retrieving this concept from Weber's late writings, we argue that the fundamental basis of the orders sociologists seek to understand is not chaos. Action is rendered interpretable, rather, to the extent persons orient themselves to possibilities and probabilities, which remain real but unknowable. In this framework, interpretation and probability are allies, not antagonists. Weber's systematic use of the probabilistic notion of Chance as a central resource for concept formation and sociological explanation seriously challenges current understandings of probability as a purely statistical, atheoretical concern. We outline the conceptual difference it makes when basic categories of sociology are understood as rooted in Chance, and we point to the larger implications of Weber's probabilism for contemporary debates around issues of prediction, action, and interpretation.